Green Synthesis, Characterization, and Catalytic Activity of Amine-multiwalled Carbon Nanotube for Biodiesel Production - Rugi Vicente Rubi; Armando Quitain; Tetsuya Kida; Raymond Tan; Luis Razon; Joseph Auresenia; Maria Cristina Arboleda Macawile; Alva Durian (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
An amine-functionalized multiwalled carbon nanotube (MWCNT) was prepared for use as a basic heterogeneous catalyst for the conversion of Cocos nucifera (coconut) oil and Hibiscus cannabinus (kenaf) oil to biodiesel. The 3-aminopropyltrimethoxysilane (3-APTMS) was chosen to form an amine-reactive surface to bind with hydroxyl (−OH) and carboxyl (−COOH) groups of oxidized MWCNT. Silanization took place using a green surface modification method in which supercritical carbon dioxide fluid was utilized under the following conditions: 55 °C, 9 MPa, and 1 h. The synthesized catalyst was characterized using Thermogravimetric analysis (TGA), Fourier transform infrared (FTIR), Field emission scanning electron microscopy–energy dispersive x-ray (FESEM-EDX), Time-of-flight secondary ion mass spectrometry (TOF-SIMS), X-ray powder diffraction (XRD), and Brunauer–Emmett-Teller (BET). Transesterification of coconut oil using 10 wt% NH2-MWCNT catalyst (3 wt% APTMS), 12:1 molar ratio of methanol and oil at 63 °C for 1 h resulted in a >95% conversion. On the other hand, the same catalyst was used in the transesterification of kenaf oil, and formation of ammonium carboxylated salt was observed. The effects of temperature, pressure, and silane concentration on surface modification of MWCNT were evaluated in terms of the catalyst’s basic site density and fatty acid methyl ester conversion. The results indicate that reaction temperature and silane concentration had the most significant effects. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).